PATANJALI: BENCHMARK FOR THE INDIAN ENTREPRENEURS. (International Journal of Food and Nutritional Sciences, 2022)
Patanjali is a company which gives a tough competition to its other market competitors like Dabur, HUL, Emami etc., following Indian traditional protocols. Indigenous company boost not only the nation’s economy but also helps in motivating people as a nationalism factor grows in them. Baba Ramdev and Acharya Balkrishna in 2006 established PAL (Patanjali Ayurved limited) with the one big objective of establishing the science of Ayurveda with the blend of modern techniques and ancient wisdom. Today Patanjali stand among the top most FMCG companies or ahead of some of the major players in FMCG market. This study will focus on the marketing strategies of the Patanjali products, the data are compiled by face to face conversation, based on the questionnaire, with the sample size of 300 consumers at DELHI NCR. Analysis is done while using mean-based ranks and one sample t-test, the study concluded the most influencing factors affecting customer’s preference for Patanjali product are price, quality and health consciousness. This study is useful for business in market as now a-days the companies are trying to go in herbal or 100% natural product zone due to the increase in the demand of health related products over the chemical driven in FMCG market.